PELATIHAN DAN PENDAMPINGAN PEMBUATAN BIBIT JAMUR TIRAM DI DESA TONDOK BAKARU MAMASA SULAWESI BARAT - Muis, Nurmuliayanti; Hidayah, Nurul; Syamsidah, Syamsidah; Jumadi, Oslan; Taufieq, Nur Anny S.; Indra, Indra; Wahid, Masyitha; Arifin, Asia; Rosman N., Andi (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2025)
One of the challenges in oyster mushroom cultivation faced by the Andika Makmur Sejahtera Farmer Group in Tondok Bakaru Village, Mamasa Regency, is the limited access to oyster mushroom spawn. The community's lack of knowledge and understanding related to spawn production, compounded by limited equipment and facilities, necessitates the importation of oyster mushroom spawn from outside the island of Sulawesi. This situation affects the efficiency of the production process and results in high costs. To address this challenge, a team from Universitas Sulawesi Barat, supported by a team from Universitas Negeri Makassar, provided training and assistance in producing F0, F1, and F2 oyster mushroom spawn to members of the oyster mushroom farmer group in Tondok Bakaru Village. The aim of this community service program is to equip farmer group members with the skills and knowledge required for producing oyster mushroom spawn and using the necessary equipment. The program began with a field observation of the target partner’s conditions, both in person and through remote communication. This was followed by a coordination phase between the implementation team and the supporting team regarding the planned community service activities. The implementation phase included the delivery of materials on oyster mushroom spawn production techniques, accompanied by demonstrations and hands-on practice by farmer group members. The program concluded with monitoring and evaluation to assess the program's success. The training and assistance activities resulted in an 85.22% increase in community knowledge, indicating that these activities were effective in supporting the progress of oyster mushroom cultivation in Tondok Bakaru Village. Salah satu tantangan budidaya jamur tiram yang dialami oleh Kelompok Tani Andika Makmur Sejahtera di Desa Tondok Bakaru, Kabupaten Mamasa adalah sulitnya akses untuk memperoleh bibit jamur tiram. Kurangnya pengetahuan dan pemahaman masyarakat terkait pembuatan bibit, ditambah dengan minimnya fasilitas peralatan yang dimiliki sehingga bibit jamur tiram harus didatangkan dari luar Pulau Sulawesi. Hal ini berdampak pada kurang maksimalnya proses produksi dan tingginya biaya yang dikeluarkan. Untuk menjawab tantangan tersebut, tim Universitas Sulawesi Barat didampingi oleh tim Universitas Negeri Makassar memberikan pelatihan dan pendampingan pembuatan bibit jamur tiram F0, F1, dan F2 kepada anggota kelompok tani jamur tiram di Desa Tondok Bakaru. Tujuan program pengabdian ini adalah untuk membekali anggota kelompok tani kemampuan dan keterampilan dalam membuat bibit jamur tiram dan menggunakan peralatan pendukung. Tahapan kegiatan dimulai dari observasi kondisi mitra sasaran secara langsung di lapangan dan melalui komunikasi jarak jauh. Dilanjutkan dengan tahapan koordinasi antara tim pelaksana dan tim pendamping terkait rencana kegiatan pengabdian yang akan dilakukan. Tahapan implementasi kegiatan dilakukan dengan pemberian materi terkait teknik pembuatan bibit jamur tiram yang dilanjutkan dengan demonstrasi dan praktik langsung oleh anggota kelompok tani. Program pengabdian ini diakhiri dengan monitoring dan evaluasi terhadap keberhasilan program yang telah dilaksanakan. Kegiatan pelatihan dan pendampingan memberikan peningkatan pengetahuan Kelompok Tani Andika Makmur Sejahtera hingga 85,22% yang menunjukkan bahwa kegiatan pelatihan dan pendampingan pembuatan jamur tiram ini efektif untuk mendukung kemajuan proses budidaya jamur tiram di Desa Tondok Bakaru.